2010
DOI: 10.1093/jxb/erq286
|View full text |Cite
|
Sign up to set email alerts
|

The olive DGAT2 gene is developmentally regulated and shares overlapping but distinct expression patterns with DGAT1

Abstract: Diacylglycerol acyltransferases (DGATs) catalyse the final step of the triacylglycerol (TAG) biosynthesis of the Kennedy pathway. Two major gene families have been shown to encode DGATs, DGAT1 (type-1) and DGAT2 (type-2). Both genes encode membrane-bound proteins, with no sequence homology to each other. In this study, the molecular cloning and characterization of a type-2 DGAT cDNA from olive is presented. Southern blot analysis showed that OeDGAT2 is represented by a single copy in the olive genome. Comparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
56
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 61 publications
7
56
0
Order By: Relevance
“…(Wilson et al 2001;Monteros et al 2008;Ha et al 2010;Li et al 2011;Chen et al 2012) and olive (Olea europaea L.) (Poghosyan et al 1999;Hernández et al 2005;Banilas et al 2011). With respect to genes involved in the fatty acid biosynthesis in oil palm, Nakkaew et al (2008) identified and cloned the gene of biotin carboxylase (accD) from E. guineensis which is involved in the first step of the fatty acid synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…(Wilson et al 2001;Monteros et al 2008;Ha et al 2010;Li et al 2011;Chen et al 2012) and olive (Olea europaea L.) (Poghosyan et al 1999;Hernández et al 2005;Banilas et al 2011). With respect to genes involved in the fatty acid biosynthesis in oil palm, Nakkaew et al (2008) identified and cloned the gene of biotin carboxylase (accD) from E. guineensis which is involved in the first step of the fatty acid synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…DGAT1 proteins are predicted to possess six or more transmembrane domains and belong to the membrane-bound O-acyltransferase family (Cases et al, 1998). Forward and reverse genetic approaches have confirmed that the Arabidopsis thaliana DGAT1 gene affects the TAG levels in seeds (Routaboul et al, 1999;Zou et al, 1999;Jako et al, 2001), and DGAT1 genes have been studied in detail in several species (Lung and Weselake, 2006;Shockey et al, 2006;Banilas et al, 2011). Structurally, DGAT2 proteins differ from DGAT1 and possess only two to three predicted transmembrane domains (Yen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Further, studies have shown that the DGAT2s play a critical role in the accumulation of unusual FAs (such as epoxy and hydroxy fatty acids) in castor bean (Kroon et al 2006), tung tree (Shockey et al 2006) and Vernonia (Li et al 2010a). In addition, temporal and spatial expression patterns of DGAT1s and DGAT2s among organs or in different stages of seed development often display obvious differences (Li et al 2010b;Banilas et al 2011;Xu et al 2011). However, little is known about the functional similarity or divergence of DGAT1 and DGAT2 during the pathway of storage lipid biosynthesis in planta.…”
Section: Introductionmentioning
confidence: 99%